Littératies multimodales et perspectives critiques - Diane Dagenais (Recherches en didactique des langues et des cultures)
This article examines how literacy has developed as a construct in recent years and in particular how terms such as multiliteracies, multilingual literacies, multiliterate repertoire, multimodality and multimodal literacies have evolved in English language scholarship and in some recent publications in French. The discussion highlights how research on literacy practices based on a critical perspective have contributed to identifying more equitable pedagogical approaches for learners of diverse linguistic and cultural origins. These pedagogies enable learners to represent themselves using a greater variety of modes of expression and develop their communicative practices in a society that is increasingly heterogeneous and technological. In this text, a critical perspective is applied to the analysis of a few data excerpts from a project focused on the production and exchange of videos between bilingual and multilingual children living in different countries. This illustrates how a critical perspective can serve as a heuristic device to identify which material and social conditions might facilitate or impede learning concerning pedagogical innovation focused on multimodal literacies.